2006
DOI: 10.1098/rsbl.2006.0482
|View full text |Cite
|
Sign up to set email alerts
|

Intersex in the clam Scrobicularia plana : a sign of endocrine disruption in estuaries?

Abstract: The phenomenon of endocrine disruption is currently a source of growing concern. Feminization of male fish in UK rivers has been shown to occur extensively and has been linked with exposure to endocrine-disrupting compounds present in the environment. Much less is known of the extent and scale of endocrine disruption in estuarine and marine ecosystems, particularly in invertebrates.We present evidence that intersex, in the form of ovotestis, is occurring in the common estuarine bivalve Scrobicularia plana, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 15 publications
1
43
0
1
Order By: Relevance
“…Consequently, the sex ratio between males and females decreased significantly (P \ 0.05). Chesman and Langston (2006) detected a ratio of males (without intersex) to females lower than the unity in the S. plana population from the Avon Estuary (United Kingdom), thus confirming the result obtained in this study. In the studies that reported the existence of 'hermaphrodites' in this species, the sex ratio indicated a slight predominance of females to males, however with no significant differences (Paes-da-Franca 1956; Raleigh and Keegan 2006).…”
Section: Resultssupporting
confidence: 94%
“…Consequently, the sex ratio between males and females decreased significantly (P \ 0.05). Chesman and Langston (2006) detected a ratio of males (without intersex) to females lower than the unity in the S. plana population from the Avon Estuary (United Kingdom), thus confirming the result obtained in this study. In the studies that reported the existence of 'hermaphrodites' in this species, the sex ratio indicated a slight predominance of females to males, however with no significant differences (Paes-da-Franca 1956; Raleigh and Keegan 2006).…”
Section: Resultssupporting
confidence: 94%
“…We are currently constructing a ranking system of the condition, adapted from a scoring index used to categorise different degrees of intersex in fish (Bateman et al 2004). The scheme, based on histological examination completed to date, has identified 6 stages in clams (Chesman & Langston 2006) and will be used as an additional parameter in the evaluation of intersex in future comparisons. Based on current evidence, the levels of severity and frequency in S. plana populations appear to be analogous to those in fish.…”
Section: Exposedmentioning
confidence: 99%
“…Similar studies on sewage exposure have detected increased vitellogenin-like proteins in males, feminised sex ratios and low gonadosomic indices. Varying degrees of intersex also reported in over 20 % of individual bivalves ( Scrobicularia plana ) sampled from 17 out of 23 British estuaries (Gomes et al 2009 ;Chesman and Langston 2006 ) Bisphenol A (BPA) was reported to act as an estrogen receptor agonist in ramshorn snails because effects were antagonized by co-exposure to ER-antagonists (Oehlmann et al 2006 ). These results could not be replicated by Forbes et al ( 2008 ) and remain controversial Potent androgen receptor agonists and aromatase inhibitors, as well as marine anti-fouling paint component tributyl tin (TBT), induce "imposex" in female gastropod molluscs at concentrations as low as parts per billion (Horiguchi 2006 ).…”
Section: Endocrine Disruption In Invertebratesmentioning
confidence: 95%